A photothermal energy storage carbon nanotube phase change microcapsule modified TPU film and a preparation method thereof
Patent Information
- Application Number
- CN202611353050.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明针对现有TPU保暖膜仅依赖被动隔热、无法主动蓄能升温的问题,提供一种光热蓄能碳纳米管相变微胶囊改性TPU膜及其制备方法
(1)本发明通过在表层与中间层之间设置含碳纳米管和相变微胶囊的第一界面层,构建了从光热转换层到相变蓄热层的"热桥"传导路径,使碳纳米管产生的热量可高效传递至相变微胶囊进行蓄存,而非在表面局部聚集散失;同时在中间层与底层之间设置含相变微胶囊和微孔结构的第二界面层,实现了蓄热与隔热的渐变过渡,减少了热阻抗突变导致的热量反向散失。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of functional polymer thin film materials, and more specifically, relates to a photothermal energy storage carbon nanotube phase change microcapsule modified TPU film and its preparation method. Background Technology
[0002] Thermoplastic polyurethane (TPU) films are widely used in textiles, medical devices, and electronic packaging due to their excellent elasticity, abrasion resistance, weather resistance, and moisture permeability. In thermal clothing, TPU films are typically used as a waterproof and breathable layer, relying solely on passive static insulation—that is, using the material's low thermal conductivity to prevent heat loss. However, this passive insulation method cannot actively store and raise the temperature, resulting in limited warmth retention in low-temperature outdoor environments.
[0003] To achieve active heating, existing technologies have introduced photothermal conversion materials. Carbon nanotubes (CNTs) are widely used as photothermal conversion fillers due to their broad-spectrum absorption and efficient photothermal conversion properties. However, CNTs tend to aggregate and have poor dispersibility in polymer matrices, requiring surface modification. Currently used covalent modification methods (such as acidification and coupling agent grafting) can disrupt the spp properties of CNTs. 2 The conjugated structure reduces its photothermal conversion efficiency and electrical conductivity. Chinese patent CN104640916A discloses a resin composition and a molded product made using the resin composition. It utilizes a method of non-covalently modifying carbon nanotubes with polycyclic aromatic hydrocarbon derivatives through π-π stacking to improve the dispersion of CNTs. However, this patent only focuses on electromagnetic shielding and antistatic properties, and does not involve photothermal conversion applications or multilayer composite film structures.
[0004] Furthermore, existing photothermal-phase change composite films generally suffer from high thermal resistance and low energy transfer efficiency between the photothermal layer and the phase change layer. The heat generated by photothermal conversion is not efficiently transferred to the phase change microcapsules for storage, resulting in localized overheating on the surface and insufficient internal heat storage. At the same time, the abrupt interface change between the insulation layer and the heat storage layer also leads to severe reverse heat loss.
[0005] Therefore, there is an urgent need for a TPU functional film that combines active photothermal heating and phase change heat storage and temperature regulation. Summary of the Invention
[0006] This invention addresses the problem that existing TPU thermal insulation films rely solely on passive heat insulation and cannot actively store energy for heating, by providing a photothermal energy storage carbon nanotube phase change microcapsule modified TPU film and its preparation method.
[0007] The objective of this invention can be achieved through the following technical solutions: A photothermal energy storage carbon nanotube phase change microcapsule modified TPU film, wherein the TPU film has a five-layer composite structure, comprising, from the outside to the inside: The surface layer is a blend of TPU and pyrene-butyric acid-modified carbon nanotubes, wherein the pyrene-butyric acid-modified carbon nanotubes account for 3-8 wt% of the total mass of the surface layer. The first interface layer is a blend of TPU, pyrene-butyric acid-modified carbon nanotubes, and phase change microcapsules. The pyrene-butyric acid-modified carbon nanotubes account for 0.5-2 wt% of the total mass of the first interface layer, and the phase change microcapsules account for 2-5 wt% of the total mass of the first interface layer. The core material of the phase change microcapsules is selected from at least one of paraffin wax, fatty acids, and octadecane, and the wall material is a melamine resin-polyurea double-shell structure, with the melamine resin as the inner shell and the polyurea as the outer shell. The intermediate layer is a blend of TPU and the phase change microcapsules, wherein the phase change microcapsules account for 10-25 wt% of the total mass of the intermediate layer. The second interface layer is a blend of TPU, the phase change microcapsules, and a microporous structure formed by foaming pre-coated sodium bicarbonate. The phase change microcapsules account for 1-3 wt% of the total mass of the second interface layer, and the pre-coated sodium bicarbonate accounts for 1-3 wt% of the total mass of the second interface layer. The pre-coated sodium bicarbonate is a core-shell structure formed by coating the surface of sodium bicarbonate particles with TPU solution and drying it. The bottom layer is a blend of TPU and the pre-coated sodium bicarbonate foam to form a microporous structure, wherein the amount of pre-coated sodium bicarbonate is 5-15 wt% of the bottom TPU.
[0008] Furthermore, the pyrene-butyric acid-modified carbon nanotubes are obtained by one-step non-covalent modification of multi-walled carbon nanotubes through the π-π stacking interaction between the pyrene group of pyrene-butyric acid and the surface of the carbon nanotubes. The carboxyl group of pyrene-butyric acid forms hydrogen bonds with the urethane group in the TPU molecular chain, so that the carbon nanotubes form physical cross-linking points in the TPU matrix. Moreover, the carboxyl group on the surface of the carbon nanotubes modified by pyrene-butyric acid makes the surface of the carbon nanotubes weakly acidic, forming an acid-base interaction with the weakly alkaline surface of the melamine resin inner shell, thereby enhancing the interfacial bonding force between the surface layer and the first interface layer and the intermediate layer.
[0009] Furthermore, the multi-walled carbon nanotubes have an outer diameter of 10-30 nm and a length of 5-20 μm; the sodium bicarbonate has an average particle size of 20-50 μm.
[0010] The phase change temperature of the phase change microcapsule is 25-40℃, and the thermal decomposition temperature of the phase change microcapsule is ≥260℃.
[0011] Furthermore, the phase change microcapsules have an average particle size of 5-20 μm and a phase change enthalpy ≥150 J / g.
[0012] Preferably, the TPU is a polyester-type TPU with a Shore hardness of 80A-95A and a melt flow index of 5-25g / 10min at 190℃ and a load of 2.16kg.
[0013] Furthermore, the melamine resin inner shell is formed by in-situ polymerization of melamine and formaldehyde, and the polyurea outer shell is formed by interfacial polymerization of isophorone diisocyanate and ethylenediamine on the outer surface of the melamine resin shell layer. The amino groups of the polyurea outer shell form hydrogen bonds with the urethane groups of the TPU matrix.
[0014] Furthermore, the foaming refers to the decomposition and foaming of sodium bicarbonate at a temperature of 190-210℃ to form a microporous structure with a closed-cell rate of ≥85% and an average pore size of 30-80μm; the bottom layer is a core-shell structure formed by coating the surface of sodium bicarbonate particles with TPU solution and drying, with a TPU shell thickness of 1-3μm.
[0015] Furthermore, the thickness of the surface layer is 30-80 μm, the thickness of the first interface layer is 5-15 μm, the thickness of the intermediate layer is 50-150 μm, the thickness of the second interface layer is 5-15 μm, and the thickness of the bottom layer is 50-120 μm.
[0016] A second aspect of the present invention provides a method for preparing the above-mentioned photothermal energy storage carbon nanotube phase change microcapsule modified TPU film, comprising the following steps: S1. Carbon nanotubes and pyrene butyric acid are mixed in ethanol at a mass ratio of 1:0.3-0.8, ultrasonically dispersed at 60-80℃ for 2-4 hours, and the ethanol is removed by rotary evaporation to obtain pyrene butyric acid modified carbon nanotubes. S2. Using at least one of paraffin, fatty acids and octadecane as the core material, a melamine resin inner shell is first formed by in-situ polymerization, and then a polyurea outer shell is formed on the outer surface of the melamine resin shell by interfacial polymerization, thus obtaining a melamine resin-polyurea bilayer shell phase change microcapsule. S3. Disperse sodium bicarbonate particles in a DMF solution of TPU, stir, filter and dry to form a 1-3 μm thick TPU shell on the surface of sodium bicarbonate particles, and obtain pre-coated sodium bicarbonate. S4. Mix TPU with each functional filler according to the ratio, and then melt-blend and extrude granulate them separately through a twin-screw extruder to obtain surface material, first interface layer material, middle layer material, second interface layer material and bottom layer material. S5. Add the five types of granules to five single-screw extruders respectively, and form them in one step through a five-layer co-extrusion casting die. The extrusion temperature of the surface layer and the first interface layer is 170-185℃, the extrusion temperature of the middle layer and the second interface layer is 175-190℃, the extrusion temperature of the bottom layer is 190-210℃, the die temperature is 185-195℃, the casting speed is 5-15m / min, and the cooling roller temperature is 25-40℃.
[0017] Furthermore, the power of ultrasonic dispersion in step S1 is 200-400W.
[0018] Furthermore, the preparation method of the melamine resin inner shell in step S2 is as follows: melamine and formaldehyde are prepolymerized at a molar ratio of 1:2-4 at pH 8.0-9.0 and 65-75℃ for 30-60 minutes to obtain a prepolymer. The prepolymer is added to the core material emulsion, the pH of the system is adjusted to 4.0-5.0, and the temperature is raised to 60-70℃ for 2-4 hours to obtain the melamine resin inner shell.
[0019] Furthermore, the preparation method of the polyurea shell in step S2 is as follows: isophorone diisocyanate is added to the melamine resin shell microcapsule emulsion, and after stirring and dispersing, ethylenediamine is added. The molar ratio of isophorone diisocyanate to ethylenediamine is 1:0.8-1.2. The reaction is carried out at 30-50℃ for 1-3 hours to form a polyurea shell on the outer surface of the melamine resin shell layer.
[0020] Furthermore, in step S3, the concentration of TPU in the DMF solution is 5-15 wt%, and the mass ratio of sodium bicarbonate to TPU solution is 1:0.05-0.15.
[0021] Furthermore, in step S4, the surface material contains 3-8 wt% pyrene-butyric acid-modified carbon nanotubes, the intermediate layer material contains 10-25 wt% phase change microcapsules, and the bottom layer material contains 5-15 wt% pre-coated sodium bicarbonate in the bottom TPU.
[0022] The surface layer is used to absorb light energy and convert it into heat energy to form a heat-conducting network; the first interface layer is used to form a thermal bridge connection between the surface heat-conducting network and the intermediate phase change microcapsules to achieve directional guidance and storage of photothermal energy; the intermediate layer is used to store excess heat and release it slowly when cooling down; the second interface layer is used to achieve a gradual transition between heat storage and heat insulation; and the bottom layer is used for heat insulation support and to reduce heat loss.
[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) By setting a first interface layer containing carbon nanotubes and phase change microcapsules between the surface layer and the middle layer, the present invention constructs a "thermal bridge" conduction path from the photothermal conversion layer to the phase change heat storage layer, so that the heat generated by the carbon nanotubes can be efficiently transferred to the phase change microcapsules for storage, rather than being locally accumulated and dissipated on the surface; at the same time, a second interface layer containing phase change microcapsules and microporous structure is set between the middle layer and the bottom layer, realizing a gradual transition between heat storage and heat insulation, and reducing the reverse heat loss caused by the sudden change in thermal resistance.
[0024] (2) This invention discovers that pyrene-butyric acid-modified carbon nanotubes in TPU phase change microcapsule systems possess a triple mechanism of "π-π stacking dispersion + hydrogen bond interface anchoring + acid-base interface affinity": the pyrene group of pyrene-butyric acid enables the carbon nanotubes to be uniformly dispersed in TPU through π-π stacking, maintaining the sp of carbon nanotubes. 2 The conjugated structure is intact and does not reduce the photothermal conversion efficiency; the carboxyl groups of pyrene butyric acid form hydrogen bonds with the urethane groups in the TPU molecular chain, making the carbon nanotubes the physical cross-linking points in the TPU network, improving the tensile strength and washability of the composite film; the carboxyl groups make the surface of the carbon nanotubes weakly acidic (pH=5.5-6.5), forming an acid-base interaction with the weakly alkaline surface of the melamine resin shell, enhancing the interfacial bonding force between the surface layer and the intermediate layer, and preventing interlayer delamination.
[0025] (3) This invention employs a double-shell design with a melamine resin inner shell and a polyurea outer shell. The melamine resin inner shell provides a dense cross-linked network to prevent gas molecules from escaping; the polyurea outer shell (formed by interfacial polymerization of IPDI and ethylenediamine) has higher flexibility and a higher Tg, buffering thermal expansion stress. The two mechanisms work synergistically to increase the thermal decomposition temperature of the microcapsule from approximately 220°C for a single-layer melamine resin shell to over 260°C, ensuring the integrity of the microcapsule structure and no core material leakage at the TPU melt blending temperature (180-210°C). At the same time, the amino groups of the polyurea outer shell form hydrogen bonds with the TPU matrix, improving the interfacial bonding force between the microcapsule and the matrix and solving the problem of washing and detachment.
[0026] (4) In this invention, sodium bicarbonate particles are pre-coated with TPU solution to form a core-shell structure. During the melt blending stage, the TPU shell layer blocks heat and prevents premature decomposition of sodium bicarbonate. Sodium bicarbonate only decomposes and foams after the TPU shell layer softens and melts in the die area of co-extrusion casting (190-210℃), forming a microporous structure with a closed-cell rate of ≥85%. The closed-cell structure effectively blocks moisture intrusion, ensuring no oil seepage or peeling after 50 washes.
[0027] (5) This invention achieves one-time molding of functional layered structures through five-layer co-extrusion casting. Each layer is extruded simultaneously and melt-bonded between layers, eliminating the need for subsequent composite processes. This results in high production efficiency and strong interlayer bonding. Compared to existing solution casting methods, the melt co-extrusion process of this invention enables continuous industrial production. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described below with reference to specific embodiments, but the scope of protection of this invention is not limited thereto. Experimental methods not specifically described in the embodiments are generally performed under conventional conditions or according to the manufacturer's recommendations. Unless otherwise specified, all reagents and materials used are commercially available.
[0029] Example 1 A method for preparing a TPU film modified with carbon nanotube phase change microcapsules for photothermal energy storage includes the following steps: S1. Preparation of pyrene-butyric acid modified carbon nanotubes (CNTs) 20g of multi-walled carbon nanotubes (outer diameter 10-20nm, length 10-15μm) and 8g of pyrene-butyric acid were added to 2L of ethanol and ultrasonically dispersed at 300W for 3h at 70℃. Then, the ethanol solvent was removed by rotary evaporation to obtain pyrene-butyric acid-modified carbon nanotubes. The pH value of the modified carbon nanotube surface was measured to be 6.0.
[0030] S2, Preparation of high-temperature resistant phase change microcapsules (1) Preparation of melamine resin inner shell: 10g of melamine and 25mL of 37% formaldehyde solution were added to 100mL of deionized water. The pH was adjusted to 8.5 with triethanolamine, and the mixture was stirred at 70℃ for 40min until the solution was clear and transparent. 9g of urea was added and stirring was continued until the solution was clear to obtain melamine resin prepolymer. 80g of n-octadecane was heated to 60℃ to melt, and then added to 200mL of deionized water containing 2g of sodium dodecyl sulfate. The mixture was emulsified at high speed for 30min (15000rpm) to form an O / W emulsion. The prepolymer was added dropwise to the emulsion, and the pH was adjusted to 4.5 with citric acid. The mixture was reacted at 65℃ for 3h to form a melamine resin inner shell microcapsule emulsion.
[0031] (2) Preparation of polyurea shell: 5g of isophorone diisocyanate (IPDI) was added to the above microcapsule emulsion and stirred for 20min. Then, 2.4g of ethylenediamine (IPDI to ethylenediamine molar ratio 1:1) was added, and the mixture was reacted at 40℃ for 2h to form a polyurea shell on the outer surface of the melamine resin shell. After filtration, washing with water, and vacuum drying at 60℃ for 12h, melamine resin-polyurea bilayer shell phase change microcapsules were obtained. The average particle size of the microcapsules was approximately 8μm, the phase change temperature was 28.5℃, the phase change enthalpy was 172J / g, and the thermal decomposition temperature was 268℃.
[0032] S3. Preparation of pre-coated sodium bicarbonate 30g of sodium bicarbonate (average particle size 35μm) was dispersed in 300mL of DMF solution containing 15g of TPU (TPU concentration 5wt%), stirred at room temperature for 30min, filtered, and then vacuum dried at 50℃ for 6h to form a TPU shell layer of about 2μm thickness on the surface of sodium bicarbonate particles.
[0033] S4, blending and granulation Five types of granules were prepared using polyester-based TPU (Shore hardness 85A, melt flow index 15g / 10min) according to the following proportions (parts by weight, based on a total mass of 100 parts per layer): Surface material: 95 parts TPU + 5 parts pyrene-butyric acid modified carbon nanotubes; First interface layer material: 96 parts TPU + 1 part pyrene-butyric acid modified carbon nanotubes + 3 parts phase change microcapsules; Intermediate layer material: 82 parts TPU + 18 parts phase change microcapsules; Second interface layer material: 96.5 parts TPU + 2 parts phase change microcapsules + 1.5 parts pre-coated sodium bicarbonate; Base material: 90 parts TPU + 10 parts pre-coated sodium bicarbonate.
[0034] Each layer of material is melt-blended and extruded and granulated using a twin-screw extruder. The extrusion temperature of the surface layer and the first interface layer is 175℃, the extrusion temperature of the middle layer and the second interface layer is 185℃, and the extrusion temperature of the bottom layer is 185℃, to ensure that the TPU shell remains intact and that sodium bicarbonate does not decompose prematurely.
[0035] S5, five-layer co-extrusion casting Five types of granules were added to five single-screw extruders. The extrusion temperature of the surface layer and the first interface layer was 175℃; the extrusion temperature of the middle layer and the second interface layer was 185℃; the extrusion temperature of the bottom layer was 200℃, which softened and melted the TPU shell layer and caused sodium bicarbonate to decompose and foam in situ; the die temperature was 190℃, the casting speed was 10m / min, and the cooling roller temperature was 30℃.
[0036] The total thickness of the resulting TPU film is approximately 200 μm, including a surface layer of approximately 50 μm, a first interface layer of approximately 10 μm, a middle layer of approximately 70 μm, a second interface layer of approximately 10 μm, and a bottom layer of approximately 60 μm.
[0037] Example 2 The difference between this embodiment and Embodiment 1 is that: In step S1 of this embodiment, the amount of pyrene-butyric acid added is 10g and the amount of multi-walled carbon nanotubes is 20g, that is, the mass ratio of multi-walled carbon nanotubes to pyrene-butyric acid is 1:0.5. In step S4, the surface material is: 93 parts TPU + 7 parts pyrene-butyric acid modified CNTs; The intermediate layer material consists of: 78 parts TPU + 22 parts phase change microcapsules; The base material consists of 88 parts TPU and 12 parts pre-coated sodium bicarbonate. The bottom layer extrusion temperature is 205℃.
[0038] The total thickness of the resulting TPU film is approximately 250 μm, including a surface layer of approximately 60 μm, a first interface layer of approximately 12 μm, a middle layer of approximately 90 μm, a second interface layer of approximately 12 μm, and a bottom layer of approximately 76 μm.
[0039] Example 3 The difference between this embodiment and Embodiment 1 is that: In step S2 of this embodiment, the core material is a mixture of paraffin wax (melting point 32℃) and stearic acid in a mass ratio of 7:3, wherein the paraffin wax is 56g, the stearic acid is 24g, and the total mass of the core material is 80g; the final phase change microcapsules have an average particle size of about 12μm, a phase change temperature of 33.2℃, and a phase change enthalpy of 165J / g. In step S4, the first interface layer material is: 94 parts TPU + 1.5 parts pyrene-butyric acid modified CNTs + 4.5 parts phase change microcapsules; The second interface layer material consists of: 95 parts TPU + 2.5 parts phase change microcapsules + 2.5 parts pre-coated sodium bicarbonate.
[0040] The final TPU film has a total thickness of approximately 180 μm, including a surface layer of approximately 40 μm, a first interface layer of approximately 8 μm, a middle layer of approximately 60 μm, a second interface layer of approximately 8 μm, and a bottom layer of approximately 64 μm.
[0041] Comparative Example 1 Compared with Example 1, this comparative example differs in that it does not have a first interface layer and a second interface layer, but only a three-layer structure (top layer + middle layer + bottom layer), which is co-extruded and cast. The formulations of the top layer, middle layer, and bottom layer are the same as those in Example 1.
[0042] Comparative Example 2 Compared with Example 1, the difference of this comparative example is that this comparative example does not have the pyrene butyric acid modification in step S1, that is, the multi-walled carbon nanotubes are used directly without modification; in step S4, the surface material is: 95 parts TPU + 5 parts carbon nanotubes; the first interface layer material is: 96 parts TPU + 1 part carbon nanotubes + 3 parts phase change microcapsules.
[0043] Comparative Example 3 Compared with Example 1, the difference of this comparative example is that in step S2 of this comparative example, the polyurea shell is not prepared, and only the melamine resin monolayer shell microcapsule is retained.
[0044] Comparative Example 4 Compared to Example 1, this comparative example differs in that step S2 does not involve the preparation of a melamine resin inner shell. Instead, polyurea monolayer shell microcapsules are directly formed on the surface of the core material emulsion via interfacial polymerization. Specifically, 80g of n-octadecane is heated to 60°C to melt, and then added to 200mL of deionized water containing 2g of sodium dodecyl sulfate. The mixture is emulsified at high speed for 30 minutes (15000rpm) to form an O / W emulsion. 8g of isophorone diisocyanate (IPDI) is added to the emulsion, and the mixture is stirred and dispersed for 20 minutes. Then, 3.8g of ethylenediamine (IPDI to ethylenediamine molar ratio 1:1) is added, and the mixture is reacted at 40°C for 3 hours, directly forming a polyurea monolayer shell on the surface of the core material droplets. After filtration, washing with water, and vacuum drying at 60°C for 12 hours, monolayer polyurea shell phase change microcapsules are obtained. The microcapsules have an average particle size of 7μm, a phase change temperature of 28.2°C, a phase change enthalpy of 158J / g, and a thermal decomposition temperature of 238°C.
[0045] Comparative Example 5 Compared with Example 1, this comparative example differs in that step S3 (preparation of pre-coated sodium bicarbonate) is omitted, and uncoated sodium bicarbonate particles (average particle size 35 μm) are used directly to replace the pre-coated sodium bicarbonate. The remaining steps and formulations are the same as in Example 1.
[0046] Performance testing methods I. FTIR Analysis 1. A Bruker Tensor 27 Fourier transform infrared spectrometer was used in ATR mode, with a scanning range of 4000-600 cm⁻¹. -1 4cm resolution -1 The scan was performed 32 times. FTIR tests were conducted on the pure TPU matrix, the intermediate layer of Example 1 (TPU + phase change microcapsules), the intermediate layer of Comparative Example 3, and the intermediate layer of Comparative Example 4, respectively. The results showed that the NH stretching vibration peak of the intermediate layer of Example 1 increased from 3328 cm⁻¹. -1 Shifting towards lower wavenumbers to 3302 cm -1This indicates that the free NH groups of the polyurea shell formed hydrogen bonds with the C=O groups of the TPU urethane groups. Simultaneously, the proportion of hydrogen-bonded C=O increased from 0.42 in pure TPU to 0.58, indicating that a large number of new hydrogen bonds were formed between the NH groups of the polyurea shell and the C=O groups of the TPU. The proportion of hydrogen-bonded C=O in Comparative Example 3 was only 0.45, slightly higher than that of pure TPU. This is because although the melamine resin shell surface has a small number of -NH2 groups, their density is much lower than that of the polyurea shell. The proportion of hydrogen-bonded C=O in Comparative Example 4 was 0.47, slightly higher than that of Comparative Example 3 but significantly lower than that of the double-shell structure in Example 1. This indicates that without the support of the melamine resin inner shell, the interfacial contact area and orientation order between the polyurea shell and the TPU decrease, leading to a decrease in hydrogen bond formation efficiency. The proportion of hydrogen-bonded C=O was calculated using the following formula: R = A1 / (A1 + A2), where A1 and A2 are the 1710-1730 cm⁻¹ values obtained through peak fitting (Gaussian-Lorentzian function), respectively. -1 The integral peak area of hydrogen bonding and free C=O stretching vibration peaks within the interval.
[0047] 2. FTIR comparison tests were performed on the surface layer of Example 1 (TPU + pyrene-butyric acid modified carbon nanotubes) and the surface layer of Comparative Example 2. The results showed that in the surface layer of Example 1, the C=O peak of the carboxyl group of pyrene-butyric acid decreased from 1698 cm⁻¹. -1 (Comparative Example 2, case where the surface layer is not modified with carbon nanotubes) Displaced to 1688 cm⁻¹ -1 This indicates that the carboxyl groups formed hydrogen bonds with the NH groups of TPU. Simultaneously, the proportion of hydrogen-bonded C=O significantly increased from 0.43 to 0.61, while in Comparative Example 2 the proportion was only 0.43, indicating no significant hydrogen bonding between unmodified CNTs and TPU. Furthermore, the significant enhancement of the NH stretching vibration peak in the surface layer of Example 1 further confirms that a hydrogen bond network was formed between the carboxyl groups on the surface of pyrene-butyric acid-modified carbon nanotubes and the NH groups of the TPU urethane groups, making the carbon nanotubes physical crosslinking points within the TPU matrix.
[0048] II. The following performance tests were performed on the TPU films obtained in the above embodiments and comparative examples: Test 1: Photothermal conversion performance Under still air (natural convection) conditions, using an AM1.5G standard solar simulator (spectral range 280-2500nm, conforming to IEC60904-9 standard), at 1 Sun (100mW / cm²), 2 Under simulated sunlight irradiation, the sample size was 5cm × 5cm, and the thickness was the actual film thickness. An infrared thermal imager was used to record the change in film surface temperature over time. The time required for the film surface to reach a steady-state temperature and the photothermal conversion efficiency were determined. The photothermal conversion efficiency η (%) was calculated using the following formula: η=[h×A×(T1-T0)] / (P×A)×100%=h×(T1-T0) / P×100% Where: h is the convective heat transfer coefficient (W / (m²)) 2 The slope of the temperature-time curve during the cooling phase is obtained through the heat balance equation: h = m × Cp / (A × τ), where m is the sample mass, Cp is the sample specific heat capacity, τ is the cooling time constant (obtained by fitting T(t) = T0 + (T1 - T0) × exp(-t / τ)); and A is the light-receiving area of the sample (m²). 2 T1 is the steady-state surface temperature (°C); T0 is the ambient temperature (°C); P is the incident light power density (100 mW / cm²). 2 =1000W / m 2 ).
[0049] Test 2: Phase Change Thermal Storage Performance The composite membrane was heated from 0°C to 60°C at a heating rate of 10°C / min under a nitrogen atmosphere using differential scanning calorimetry (DSC). The DSC curves were recorded, and the phase transition enthalpy ΔH of the membrane was determined. The phase transition enthalpy ΔH (J / g) was calculated using the following formula: ΔH=∫(dQ / dt)dt / m Where: ∫(dQ / dt)dt is the area of the phase transition peak on the DSC curve, which is obtained by integrating after baseline correction of the endothermic peak within the phase transition temperature range. The baseline adopts the linear baseline method (the line connecting the phase transition start temperature and the end temperature is used as the baseline); m is the mass of the DSC test sample (mg).
[0050] The actual phase transition enthalpy ΔH1 of the microcapsules is calculated based on the mass fraction w of the microcapsules in the composite membrane: ΔH1 = ΔH / w × 100%.
[0051] Test 3: Temperature resistance of microcapsules After heat-treating the granules of each embodiment and comparative example at 185°C for 10 min, the integrity of the microcapsule morphology was observed.
[0052] Test 4: Washability According to GB / T8629-2017 standard, after 50 standard washing cycles, the TPU film was tested for surface oil seepage and microcapsule detachment.
[0053] Test 5: Comprehensive performance of solar thermal, heat storage, and thermal insulation Under ambient temperature of -5℃, using an AM1.5G standard solar simulator (spectral range 280-2500nm, conforming to IEC60904-9 standard), at 1 Sun (100mW / cm²), 2Under simulated continuous sunlight irradiation, the temperature change of the inner side (bottom layer side) of the membrane over time was measured to evaluate the synergistic effect of photothermal heat generation, phase change heat storage and foam insulation.
[0054] The test results are shown in Tables 1 and 2.
[0055] Table 1
[0056] Table 2
[0057] As can be seen from the test results in Table 1, compared with Comparative Examples 1-5, Examples 1-3 significantly improved washability, heat insulation and other properties through the triple interface mechanism of pyrene-butyric acid-modified CNTs, hydrogen bond anchoring of polyurea shell and controlled-release foaming of pre-coated sodium bicarbonate, resulting in better overall performance.
[0058] In Comparative Example 1, which lacks an interface layer, the heat generated by the carbon nanotubes accumulates on the surface and fails to be efficiently transferred to the intermediate layer for storage. This significantly reduces the photothermal-heat storage synergy efficiency and prolongs the time required to reach the steady-state temperature (120 seconds vs. 85 seconds in Example 1).
[0059] Comparative Example 2 showed severe agglomeration and uneven dispersion of unmodified carbon nanotubes, resulting in the lowest photothermal conversion efficiency and the longest time required to reach steady-state temperature (145s). Furthermore, due to the unmodified carbon nanotubes and weak interfacial bonding with TPU, Comparative Example 2 exhibited significant carbon nanotube detachment after washing, leading to low tensile strength retention.
[0060] Although the single-layer melamine resin shell microcapsules of Comparative Example 3 have high density, their thermal decomposition temperature is about 220°C. After heat treatment at 185°C, some shell layers have cracked, resulting in core material leakage. After washing, oil seepage and detachment occur. This is because the cross-linked network of melamine resin loses water and degrades at high temperature.
[0061] The thermal decomposition temperature of the single-layer polyurea shell microcapsule in Comparative Example 4 is approximately 238°C, which is higher than that of the single-layer melamine resin shell, but still lower than the 260°C of the double-shell structure. This is because the polyurea network formed by IPDI and ethylenediamine has a higher porosity, resulting in poorer sealing of the core material compared to melamine resin. Furthermore, due to the lack of dense shielding effect from the melamine resin inner shell, a small amount of shell cracking occurred during heat treatment at 185°C, leading to slight oil leakage and minor detachment. In contrast, the melamine resin-polyurea double-shell design of this application combines the high density shielding of the inner shell (melamine resin) with the high thermal stability and TPU hydrogen bond anchoring properties of the outer shell (polyurea). The synergy of these two factors allows the thermal decomposition temperature to exceed 260°C.
[0062] Comparative Example 5, due to the lack of pre-coating of sodium bicarbonate, decomposed prematurely during the blending stage, resulting in a high porosity and uneven pore size distribution in the bottom microporous structure. After moisture intrusion, the microcapsule interface was destroyed, resulting in a small amount of detachment and a decrease in thermal insulation performance.
[0063] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A photothermal energy storage carbon nanotube phase change microcapsule modified TPU film, characterized in that, The TPU film has a five-layer composite structure, comprising, from the outside in, the following layers: The surface layer is a blend of TPU and pyrene-butyric acid-modified carbon nanotubes, wherein the pyrene-butyric acid-modified carbon nanotubes account for 3-8 wt% of the total mass of the surface layer. The first interface layer is a blend of TPU, pyrene-butyric acid-modified carbon nanotubes, and phase change microcapsules. The pyrene-butyric acid-modified carbon nanotubes account for 0.5-2 wt% of the total mass of the first interface layer, and the phase change microcapsules account for 2-5 wt% of the total mass of the first interface layer. The core material of the phase change microcapsules is selected from at least one of paraffin wax, fatty acids, and octadecane, and the wall material is a melamine resin-polyurea double-shell structure, with the melamine resin as the inner shell and the polyurea as the outer shell. The intermediate layer is a blend of TPU and the phase change microcapsules, wherein the phase change microcapsules account for 10-25 wt% of the total mass of the intermediate layer. The second interface layer is a blend of TPU, the phase change microcapsules, and a microporous structure formed by foaming pre-coated sodium bicarbonate. The phase change microcapsules account for 1-3 wt% of the total mass of the second interface layer, and the pre-coated sodium bicarbonate accounts for 1-3 wt% of the total mass of the second interface layer. The pre-coated sodium bicarbonate is a core-shell structure formed by coating the surface of sodium bicarbonate particles with TPU solution and drying it. The bottom layer is a blend of TPU and the pre-coated sodium bicarbonate foam to form a microporous structure, wherein the amount of pre-coated sodium bicarbonate is 5-15 wt% of the bottom TPU.
2. The photothermal energy storage carbon nanotube phase change microcapsule modified TPU film according to claim 1, characterized in that, The multi-walled carbon nanotubes have an outer diameter of 10-30 nm and a length of 5-20 μm; the sodium bicarbonate has an average particle size of 20-50 μm; the phase change microcapsules have a phase change temperature of 25-40 °C and a thermal decomposition temperature of ≥260 °C; the phase change microcapsules have an average particle size of 5-20 μm and a phase change enthalpy of ≥150 J / g.
3. The photothermal energy storage carbon nanotube phase change microcapsule modified TPU film according to claim 1, characterized in that, The melamine resin inner shell is formed by in-situ polymerization of melamine and formaldehyde, and the polyurea outer shell is formed by interfacial polymerization of isophorone diisocyanate and ethylenediamine on the outer surface of the melamine resin shell layer. The amino groups of the polyurea outer shell form hydrogen bonds with the urethane groups of the TPU matrix.
4. The TPU film modified with carbon nanotube phase change microcapsules for photothermal energy storage according to claim 1, characterized in that, The foaming refers to the decomposition and foaming of sodium bicarbonate at a temperature of 190-210℃ to form a microporous structure with a closed-pore rate of ≥85% and an average pore size of 30-80μm; the bottom layer is a core-shell structure formed by coating the surface of sodium bicarbonate particles with TPU solution and drying it, with a TPU shell thickness of 1-3μm.
5. The TPU film modified with carbon nanotube phase change microcapsules for photothermal energy storage according to claim 1, characterized in that, The thickness of the surface layer is 30-80 μm, the thickness of the first interface layer is 5-15 μm, the thickness of the intermediate layer is 50-150 μm, the thickness of the second interface layer is 5-15 μm, and the thickness of the bottom layer is 50-120 μm.
6. The method for preparing a photothermal energy storage carbon nanotube phase change microcapsule modified TPU film according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Carbon nanotubes and pyrene butyric acid are mixed in ethanol at a mass ratio of 1:0.3-0.8, ultrasonically dispersed at 60-80℃ for 2-4 hours, and the ethanol is removed by rotary evaporation to obtain pyrene butyric acid modified carbon nanotubes. S2. Using at least one of paraffin, fatty acids and octadecane as the core material, a melamine resin inner shell is first formed by in-situ polymerization, and then a polyurea outer shell is formed on the outer surface of the melamine resin shell by interfacial polymerization, thus obtaining a melamine resin-polyurea bilayer shell phase change microcapsule. S3. Disperse sodium bicarbonate particles in a DMF solution of TPU, stir, filter and dry to form a 1-3 μm thick TPU shell on the surface of sodium bicarbonate particles, and obtain pre-coated sodium bicarbonate. S4. Mix TPU with each functional filler according to the ratio, and then melt-blend and extrude granulate them separately through a twin-screw extruder to obtain surface material, first interface layer material, middle layer material, second interface layer material and bottom layer material. S5. The five types of granules are added to five single-screw extruders respectively, and formed in one step through a five-layer co-extrusion casting die to obtain the TPU film.
7. The preparation method according to claim 6, characterized in that, In step S5, the extrusion temperature of the surface layer and the first interface layer is 170-185℃, the extrusion temperature of the intermediate layer and the second interface layer is 175-190℃, the extrusion temperature of the bottom layer is 190-210℃, the die head temperature is 185-195℃, the casting speed is 5-15m / min, and the cooling roller temperature is 25-40℃.
8. The preparation method according to claim 6, characterized in that, The power of ultrasonic dispersion in step S1 is 200-400W; The preparation method of the melamine resin inner shell in step S2 is as follows: melamine and formaldehyde are prepolymerized at a molar ratio of 1:2-4 at pH 8.0-9.0 and 65-75℃ for 30-60 minutes to obtain a prepolymer. The prepolymer is added to the core material emulsion, the pH of the system is adjusted to 4.0-5.0, and the temperature is raised to 60-70℃ for 2-4 hours to obtain the melamine resin inner shell.
9. The preparation method according to claim 6, characterized in that, The preparation method of the polyurea shell in step S2 is as follows: isophorone diisocyanate is added to the melamine resin shell microcapsule emulsion, and after stirring and dispersing, ethylenediamine is added. The molar ratio of isophorone diisocyanate to ethylenediamine is 1:0.8-1.
2. The reaction is carried out at 30-50℃ for 1-3 hours to form a polyurea shell on the outer surface of the melamine resin shell layer.
10. The preparation method according to claim 9, characterized in that, In step S3, the concentration of TPU in the DMF solution is 5-15 wt%, and the mass ratio of sodium bicarbonate to TPU solution is 1:0.05-0.15; In step S4, the surface material contains 3-8 wt% pyrene-butyric acid-modified carbon nanotubes, the intermediate layer material contains 10-25 wt% phase change microcapsules, and the bottom layer material contains 5-15 wt% pre-coated sodium bicarbonate in the bottom TPU.
Citation Information
Patent Citations
Resin composition containing carbon nanomaterial and plastic molded product
CN104640916A